Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver. Issue 13 (1st July 2022) - Liu, Sheng-Yue; Wang, Li-Zhi; Wang, Yue-Fei; Li, Lin; Han, Guo-Ying; Zhang, Bing-Yang; Guo, Ying; He, Yong-Zhi; Fang, Shi-Ming; Zhang, Han
Abstract: Two new chroman-4-ones penicichromanone A (1 ) and penicichromanone B (2 ), together with three known compounds conioxepinol C (3 ), emodin (4 ) and moniliphenone (5 ), were obtained from the endophytic fungus Penicillium chrysogenum, which was isolated from the bark of Eucommia ulmoides Oliver. The structures of 1 and 2 were elucidated by detailed analysis of HRESIMS, 1D/2D NMR and ECD spectra. All the compounds were evaluated for their anti-inflammatory activities using HEK293 cells, and compounds 1, 3, 4 and 5 exhibited significant inhibitory effects on TNF- α -stimulated NF-κB activation. Graphical Abstract: UF0001